Clinical evidence for caspofungin monotherapy in the first-line and salvage therapy of invasive Aspergillus infections - Heinz, Werner J.; Buchheidt, Dieter; Ullmann, Andrew (Mycoses, 2016)
In 2001, caspofungin received market authorisation by the FDA and EMA and is globally licensed for several indications, including candidiasis, empirical antifungal therapy in patients with neutropenic fever of unknown origin and treatment of invasive aspergillosis in patients refractory to or intolerant of amphotericin B, lipid formulations of amphotericin B or itraconazole. Despite the lack of phase III data in first-line treatment of invasive aspergillosis, increasing evidence supports the use of first-line therapy. Here, we analyse the evidence of therapeutic activity, represented by favourable response rates, of caspofungin for invasive aspergillosis. A systematic literature search was conducted to identify international presentations and papers reporting monotherapy with caspofungin. Efficacy data are summarised separately for first-line and salvage therapy. Thirty-one papers and published abstracts reported caspofungin therapy for aspergillosis. Fifteen full papers and two abstracts fulfilled the criteria of reporting significant outcome data for caspofungin monotherapy for invasive aspergillosis. Consistent with other analyses and the known safety profile, few adverse events and associated terminations of caspofungin medication have been reported. Although a randomised, comparative, prospective study using caspofungin in this indication is still lacking, growing evidence supports the efficacy of this echinocandin not only for salvage but also for first-line therapy.
Gesehen am 06.08.2019